Capacidades dinâmicas para acreditação: Evidências no setor hospitalar - Monteiro, Mariana Ribeiro (2014)
The hospital industry has been affected and pressured, in na international scale, to make management changes and reforms. As one of the ways to react to such situation, it was created the hospital accreditation, a volunteer periodic evaluation of institutional resources, based on continuous learning, aiming to guarantee assistance quality in pre-stabilized standards. For this present work, it is understood that dynamics capabilities may be created to change resources and competences of hospitals throughout a variety of sources, aiming to obtain hospital accreditation. The main objective of this research was to analyze the development of dynamics capabilities in the hospital accreditation process. Specifically, it was aimed to describe the changes occurred during the accreditation process in the light of punctuated equilibrium model; to identify the main dynamics capability in each accreditation level; characterize dynamics capability sources; and investigate capabilities lifecycle stages during the accreditation process. It was used the multiple study cases as methodological strategy, approaching two hospital with three levels of accreditation. Data was collected through semi-structured interviews, direct observation and intern documents. Data analysis to each case was held at first individually then crosses. Results evidenced that organizational change happened according to evolutionary model, under the punctuated equilibrium behavior. Three dynamic capabilities were identified in each hospital. In relation to the creation of each capability, it was understood that deliberated learning was the most utilized source, in all its mechanisms, but with different emphasis in each accreditation level. The source relationship was utilized in only to outsource, alliances and licensing, highlighting alliances with suppliers and clients. The source aquisition was not used. It is highlighted that every capacity evidenced showed adhesion to Capability Lifecycle Model suggested by Helfat and Peteraf (2003). It is concluded that all reorientation periods, many times seen as destabilizing, were the moments in which the organizations evolved indeed. This study contributes to empirical evidence of Punctuated Equilibrium and Dynamic Capability Lifecycle. Yet, the research allowed comprehending which changes occurred in the hospitals during the accreditation process and why each change was necessary. Besides, it explored the main capacities chosen by the hospitals and how they were developed, contributing to the orientation to managers in the hospital sector.